Diabetes associated with cervical carcinoma among high-risk HPV-infected patients with cytologically diagnosed high grade squamous intraepithelial lesion - Yue, Chaoyan; Zhang, Chunyi; Ying, Chunmei; Jiang, Hua (Frontiers in Endocrinology, 2022)
Background：Diabetes causes metabolic disorders and immune changes that may be potential triggers of cervical cancer. Therefore, diabetes is not a "bystander" to cervical cancer. However, the conclusion that diabetes promotes cervical cancer lacks clinical epidemiological evidence, and the reported potential association between diabetes and cervical cancer is controversial. Methods: We conducted an explorative cross-sectional study of 791 women with cytological HGSIL and HR-HPV, who attended the cervical clinic of the largest academic women's hospital in China from May 2019 to March 2022. After cervical screening, patients who were requiring colposcopy were tested for HbA1c. HbA1c level of 6.5% or higher defines diabetes and HbA1c level of 5.7%-6.4% was defined as prediabetes. The relationship between diabetes and cervical cancer was observed by a dose-response graph. Subgroup analysis and multivariate logistic regression analysis were conducted to estimate the associations between diabetes and cervical cancer. Results: Among HGSIL patients with high-risk HPV infection, compared with women with HbA1c <5.7%, the odds ratio for women with prediabetes was 1.72 (95% CI: 0.87-3.41) and the odds ratio for women with diabetes was 3.29 (95% CI: 1.10-9.80) for cervical cancer. Sensitivity analysis showed that diabetes was significantly associated with cervical cancer in different age groups and different HPV variant. E-value analysis showed robustness to unmeasured confounding. Conclusions: In patients with HR-HPV combined with HGSIL, diabetes and prediabetes are associated with cervical cancer.